Isolation and Identification Endophyte Fungi from Daun Nona Makan Sirih (Clerodendrum thomsoniae) as Antibacteril Against Bacteria Causing Skin Infection Using TLC-Bioautography - Hadjar, Aflinda; Fitriana, Fitriana; Asmaliani, Ira (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Nona makan sirih (Clerodendrum thomsoniae) contains secondary metabolites that have the potential as antibacterials. The TLC-Bioautography method will determine the antibacterial activity and chemical components of endophytic fungal isolates of nona makan sirih. This research involved the isolation of endophytic fungi from leaves of nona makan sirih using PDAC media, followed by purification and macroscopic and microscopic tests. In addition, a screening test its effect againts pathogenic bacteria. The chosen isolates were fermented for 21 days. Then supernatant and mycelia were seperated. The supernatant was extracted by dissolving ethyl acetate using the liquid-liquid ectraction method. Then extract obtained was processed by TLC with the mobile phase of chloroform:methanol (8:1) and TLC-Bioautography was carried out on bacterial tests and chemical components. The results of isolation and purification obtained as many as 13 isolates. Screening test results with IFDNMS codes 6, 8 and 11 showed activity against the test bacteria. TLC-Bioautography result isolate 6 obtained 5 spots with an Rf value of 0.89; 0.65; 0.45; 0.23; 0.05 was active against all test bacteria. Isolate 8 obtained 5 spots with an Rf value of 0.89; 0.65; 0.05 was active against all tested bacteria, while 0.45 was active against P.acnes, S.aureus, and S.epidermidis bacteria and 0.23 against S.aureus bacteria. Isolate 11 obtained 5 spots with an Rf value of 0.89; 0.61; 0.45; 0.23; 0.05 against all test bacteria. The findings indicate that flavonoids and phenolics are chemical components with antibacterial activity.